1997
DOI: 10.1302/0301-620x.79b5.7566
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Groove in the Axis Vertebra for the Vertebral Artery

Abstract: Transarticular screws at the C1 to C2 level of the cervical spine provide rigid fixation, but there is a danger of injury to a vertebral artery. The risk is related to the technical skill of the surgeon and to variations in local anatomy. We studied the grooves for the vertebral artery in 50 dry specimens of the second cervical vertebra (C2). They were often asymmetrical, and in 11 specimens one of the grooves was deep enough to reduce the internal height of the lateral mass at the point of fixation to < or =2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 0 publications
4
55
1
1
Order By: Relevance
“…Angles determined are the safe bounds for transpedicular screw fixation. These angles were found similar to the anatomical studies of Abou Madawi et al (1997a). Thus according to our results, the angle of the screw or K-wire on the horizontal plane must be between 10 -24°in the medial direction and the decline angle on the sagittal plane must be ‫°82ف‬in the cranial direction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Angles determined are the safe bounds for transpedicular screw fixation. These angles were found similar to the anatomical studies of Abou Madawi et al (1997a). Thus according to our results, the angle of the screw or K-wire on the horizontal plane must be between 10 -24°in the medial direction and the decline angle on the sagittal plane must be ‫°82ف‬in the cranial direction.…”
Section: Discussionsupporting
confidence: 91%
“…This anatomical result supports results of recent anatomical studies associated with the atlanto-axial complex. In one of these studies, it was reported that 22% of specimens had a pars interarticularis anatomy that prevented safe screw placement (Abou Madawi et al, 1997a). In another study, Paramore et al (1996) reviewed nearly 100 fine-slice axial CT scans of the atlanto-axial complex and found that 18% showed a high riding transverse foramen of the axis vertebrae on at least one side, which placed the vertebral artery at significant risk, even with ideal screw placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in C2 vertebrae the TF appears as an angulated canal: its upper opening, located more laterally than the inferior opening, forces the vertebral artery to deviate by about 45°in the sagittal plane before continuing its ascent to the C1 TF. The latter is located more laterally because the transverse process of this vertebra is larger and arises from the lateral mass (Taitz et al 1978;Abou Madawi et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The VA is classically divided into four parts: its origin (from the subclavian artery in the root of the neck) to the sixth cervical vertebra (first part); its course through the foramina transversaria of the sixth to the first cervical vertebrae (cervical/second part); from the foramen transversarium of the atlas vertebra to its passage through the dura mater at the foramen magnum (suboccipital/ third part); and its course within the cranium to the pontomedullary border (intracranial/fourth part). [1][2][3][4][5][6][7][8][9][10][11][12] The V3h portion of the VA lies close to the floor of the posterior fossa and damage to the VA may be fatal. 13,14 Therefore, before attempting surgery at the posterior fossa and craniocervical junction, a thorough anatomical study of the path of the VA is mandatory.…”
Section: Introductionmentioning
confidence: 99%